Research into the effect Of SGLT2 inhibition on left ventricular remodelling in patients with heart failure and diabetes mellitus (REFORM) trial rationale and design. Issue 1 (December 2016) - Singh, Jagdeep; Fathi, Amir; Vickneson, Keeran; Mordi, Ify; Mohan, Mohapradeep; Houston, J.; Pearson, Ewan; Struthers, Allan; Lang, Chim
Abstract Background Heart failure (HF) and diabetes (DM) are a lethal combination. The current armamentarium of anti-diabetic agents has been shown to be less efficacious and sometimes even harmful in diabetic patients with concomitant cardiovascular disease, especially HF. Sodium glucose linked co-transporter type 2 (SGLT2) inhibitors are a new class of anti-diabetic agent that has shown potentially beneficial cardiovascular effects such as pre-load and after load reduction through osmotic diuresis, blood pressure reduction, reduced arterial stiffness and weight loss. This has been supported by the recently published EMPA-REG trial which showed a striking 38 and 35 % reduction in cardiovascular death and HF hospitalisation respectively. Methods The REFORM trial is a novel, phase IV randomised, double blind, placebo controlled clinical trial that has been ongoing since March 2015. It is designed specifically to test the safety and efficacy of the SLGT2 inhibitor, dapagliflozin, on diabetic patients with known HF. We utilise cardiac-MRI, cardio-pulmonary exercise testing, body composition analysis and other tests to quantify the cardiovascular and systemic effects of dapagliflozin 10 mg once daily against standard of care over a 1 year observation period. The primary outcome is to detect the change in left ventricular (LV) end systolic and LV end diastolic volumes. The secondary outcome measures include LV ejection fraction, LV mass index, exercise tolerance, fluid status, quality of life measures and others. Conclusions This trial will be able to determine if SGLT2 inhibitor therapy produces potentially beneficial effects in patients with DM and HF, thereby replacing current medications as the drug of choice when treating patients with both DM and HF. Trial registration Clinical Trials.gov: NCT02397421. Registered 12th March 2015